Mefenamic acid inhibit transforming growth factor-beta type-1: Repurposing anti-inflammatory drugs in wound healing using in-silico approaches - Roney, Miah; Issahaku, Abdul Rashid; Normaiza, Zamri; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier B.V., 2023)
Due to low cost and time-saving benefits, drug repurposing is a safe and successful method to discover drug. A druggable target for inflammation, transforming growth factor-beta type-1 (TGF-β 1) has been identified to be associated with wound healing. Finding the most effective TGF-β 1 inhibitor among FDA-approved anti-inflammatory medications was the goal of the current investigation. To find the best hits against TGF-β 1, we used structure-based virtual screening on medications that have received FDA approval. We discovered two FDA-approved medications with notable selectivity and affinity for the binding pocket of TGF-β 1. Mefenamic acid, one of these found hits, interacts with key TGF-β 1 residues and favourably attaches to the binding pocket, requiring further study. The kinetics of the binding between mefenamic acid and TGF-β 1 were revealed by all-atom precise molecular dynamics (MD) simulations. Mefenamic acid, which may also be used as a possible lead chemical against TGF-β 1, may be a promising TGF-β 1 inhibitor.